(untitled) (American Journal of Islam and Society, 1992)
Professor Amin, who teaches international relations at Quaid-i-Azam University in Islamabad, has provided us with a short but insightful analysis of twentieth-century writings from the Liberal, Marxist, and Islamic traditions on the issue of "nationalism versus internationalism." Pointing out that Western writings treat the "nation-state" as "a universal form," he presents two main arguments: a) nationalism emerged from "Western liberal culture" and is now "seriously challenged by a variety of communitarian internationalisms," of which Islamic revivalism is the most important in the Islamic world (p. 5), and b) Islamic revivalismoften misunderstood as being a backward-looking "fundamentalism" -is "a reaction against Liberal and Marxist internationalism which are seen as the two imperialist ideologies of the West" (p. 6). Amin briefly states the essence of the three traditions-the Liberal belief in nationalism as natural, with "world unity [envisaged as emerging] through the prism of nation-states" (p. 7); the Marxist goal of a "classless world society" (p. 7); and the Islamic idea of all "believers . . . belong [ ing] to one global community, the ummah" (p. 10). Insisting that the dialogue among the three trends is facilitated by understanding all of them "from within and through their main spokesmen" (p. 10), he proceeds with a chapter on the representative literature of each. Each chapter is divided into three sections: traditional writers, modernization theorists, and postmodernization theorists. Perhaps reflecting the author’s Western education, the book’s longest chapter is the one on Liberalism. He begins with Toynbee, whom he describes as "an internationalist par excellence in the Western communitarian tradition" (p. 13). Three other Liberal writers are categorized as "traditional"-E. H. Carr, Hans Kohn, and Carleton Hayes. Under the designation of modernization theorists, Amin deals with Karl Deutsch and Ernest Gellner, while the section on post-modernization theorists looks mainly at Walker Conner and A. D. Smith. In the chapter on Marxism, Amin analyzes Marx and Engels as "traditional writers." Lenin is classified as a "modernization theorist," while ...